The multiple V-shaped double peeling of elastic thin films from elastic soft substrates. (April 2018) - Menga, N.; Afferrante, L.; Pugno, N.M.; Carbone, G.
Highlights: The periodic V-shaped double peeling of elastic films from soft elastic substrate is investigated. Adhesive strength increases with the substrate compliance. Initial small detachments can be tolerated without unstable peeling taking place. Enhancement in adhesive strength occurs when the contact is splitted in multiple smaller contacts. High resistance to detachment is obtained by properly tuning the properties of film and substrate. Abstract: In this paper, a periodic configuration of V-shaped double peeling process is investigated. Specifically, an elastic thin film is detached from a soft elastic material by applying multiple concentrated loads periodically distributed with spatial periodicity λ . The original Kendall's idea is extended to take into account the change in elastic energy occurring in the substrate when the detachment fronts propagate. The symmetric configuration typical of a V-peeling process causes the energy release rate to be sensitive to variations of the elastic energy stored in the soft substrate. This results in an enhancement of the adhesion strength because part of the external work required to trigger the peeling mechanism is converted in substrate elastic energy. A key role is played by both spatial periodicity λ and elasticity ratio E / Eh, between tape and substrate elastic moduli, in determining the conditions of stable adhesion. Indeed, the presence of multiple peeling fronts determines a modification of the mechanism of interaction, because deformations close to each peeling front are also affected by the stresses related to the other fronts. Results show that the energy release rate depends on the detached length of the tape so that conditions can be established which lead to an increase of the supported load compared to the classical peeling on rigid substrates. Finally, we also find that for any given value of the load per unit length, an optimum value of the wavelength λ exists that maximizes the tolerance of the system, before unstable propagation of the peeling front can occur.